Cultivation Of Seedlings In Vegetable Farming - Mustofokulova Feruzabonu; Xoliqova Marjona Komilovna; Kenjaev Yunus Chintoshevich (Zien Journals, 2024)
In the article, despite the high cost of growing seedlings in vegetable growing, the seedling method is economically justified, and it is widely used in vegetable growing, and in some cases it is impossible to grow vegetables. The methods and techniques of seedling cultivation, intellectually correct selection of methods of cultivation from seedlings or without seedlings are important for the economy of vegetable growing
Keywords: Nursery; open and sheltered area; planting seedlings